Potential Use of Natural Killer Cell Transfer Therapy in the Perioperative Period to Improve Oncologic Outcomes - Juan P. Cata; Claudius Conrad; Katy Rezvani (Scientifica)
Immune suppression after oncologic surgery is a common phenomenon. Several studies have demonstrated that it is associated with poor survival owing to cancer progression. Immunotherapy, especially NK cell transfer therapy, is an attractive alternative because current methodologies to isolate, generate, and expand NK cells have shown good safety profiles in current active investigations. We believe that the use of NK cell transfer therapy in the context of postoperative minimal residual disease deserves significant investigation.